Detoxification of tabun-exposed mice by an acetylcholinesterase mutant using a novel pyridinium aldoxime - Kovarik, Zrinka; Maček Hrvat, Nikolina; Žunec, Suzana; Katalinić, Maja (Biologia Serbica, 2020)
Nerve agents, such as tabun, are covalent inhibitors of acetylcholinesterase (AChE), an essential enzyme in neurotransmission whose inhibition may lead to death. Currently used therapy, consisting of an anticholinergic drug and an oxime as the reactivator of inhibited AChE is particularly ineffective in cases of tabun exposure. Thus, an optimal re-activator is still needed. Click-chemistry, utilizing Cu (I)-catalyzed azide-alkyne cycloaddition of a library of small molecule building blocks, has made possible the rapid synthesis of a variety of new oximes. Among the new oximes tested in recent studies as re-activators of tabun-inhibited choline binding site AChE mutants, oxime 5B, a lengthened alkylchain congener of the standard oxime 2-PAM, as appeared to be a candidate for tabun ex vivo scavenging when paired with the Y337A mutant of AChE. Herein, we pursued the antidotal in vivo detoxification of tabun-exposed mice by assembling oxime-assisted catalytic scavenging using the mutant combined with oxime 5B. Although the antidotal treatment requires optimization, our findings offer a platform for further development of more potent means of counteracting tabun and related phosphoramidate exposure.